Exploring the Issues and Challenges of Online Assessment and Evaluation in the Era of Artificial Intelligence (Journal of Asian Development Studies, 2024)
With the advent of artificial intelligence and sources like ChatGPT,students’ assessment and evaluation have become incredibly challenging. It has become an uphill task for teachers to ascertain the reliability of submitted assignments and other formativeassessments. Because these text generators can draft articles, make summaries, and even write codes. These text generators,at one end, have supplemented the efforts of the teachers to develop quality content and,at the other end,have equally benefittedthe students to solve the assignments and quizzes. How can teachers assess such unethical attempts? And what do they think about it?This study is aimed at exploring the challenges faced by the teachers of online/distance education institutions in the availability of artificially intelligent text generators.Qualitative research methodology has been used in this study. A grounded theory approach,as prescribed by Gioia,is employed. This methodology has been preferred because the data structure can reflect the whole research. Data have been collected from 20 teachers at higher education institutes involved in distance/online learningand classroom teachingusing semi-structured interviews.Subjects have been selected using a purposive sampling technique.Results show that AI text generators have raised concerns among teachers in the evaluation of formative assessments. Students are using such text generators to solve the assignments and other activities given tothem. However, there are some websites and software (like Turnitin) that can assess whether an assignment has been written using an AI text generator. However,these AI detectors are intheir infancy stage and do need more precision. Teachers fear that such AI can take away the creativity and writing skills ofstudents,and this technology might handicap them.This study has highlighted the concerns of academicians that need to be addressed by educationists